Future Sediment Transport Ability and its Consequences in the Urbanized River Basin - Lamichhane, Suraj; Devkota, Nirajan (Advances in Engineering and Technology: An International Journal, 2022)
The urbanization process of the Kathmandu Valley has a significant impact on LULC change, river runoff, and sediment transport capability. The historical sediment flow pattern indicates that the sediment transport capacity of the basin has increased even when precipitation and river discharge decreased. So, the sediment regression model is developed in this study in relation to discharge, precipitation, and built-up area change. Model parameters are calibrated and validated through the measured sediment discharge of the basin and the performance of the model is evaluated through NSE, PBIAS, and R2. In the future, the sediment transport capacity of the channel is projected for average monthly, maximum, and minimum flow conditions by +4.33%, +6%, and -2.66% respectively per decade due to the rise in the urban area (+6% per decade). Increasing the rigid ground surface through urbanization reduces the sediment generation through the watershed and balances the sediment transport capability, excess erosion is produced in the river channel causing a change in the river morphology. The findings of this study will be useful for planning and management of the river basin and the river structures.